Freedom [compact disc, unabridged] - Junger, Sebastian (Simon & Schuster Audio, 2021)
Throughout history, humans have been driven by the quest for two cherished ideals: community and freedom. The two don't coexist easily: we value individuality and self-reliance, yet are utterly dependent on community for our most basic needs. In this intricately crafted and thought-provoking audiobook, Sebastian Junger examines this tension that lies at the heart of what it means to be human.